2020
DOI: 10.1155/2020/2859073
|View full text |Cite
|
Sign up to set email alerts
|

Firms’ Strategic Pricing and Network Externalities

Abstract: For the sale of a product with network externalities, a Stackelberg model involving an incumbent and an entrant is developed considering the impact of three strategic decision-making modes of the incumbent and consumers on the pricing, market share, and profit of firms. In addition, the impact of consumers’ strategic behaviours on firms’ pricing decisions and how firms respond to strategic customers is discussed. The results show that, in the SS (strategic firm facing strategic consumers) decision-making mode,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The definition of network externality in Yi and Yang (2017) is that an increased number of consumers who enhance the utility gained from their own purchases by purchasing similar or compatible products. Current studies on network externalities mainly focus on product pricing (Xu et al, 2020;Zhou and Xu, 2020), product research and development (Li, 2020;Xing, 2014) and product compatibility (Choi and Lee, 2017;Li and Chen, 2012). Regarding product pricing strategies, Yi and Yang (2017) analyzed the impact of indirect network externalities on manufacturers' wholesale prices and retailers' marketing strategies.…”
Section: Network Externalitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The definition of network externality in Yi and Yang (2017) is that an increased number of consumers who enhance the utility gained from their own purchases by purchasing similar or compatible products. Current studies on network externalities mainly focus on product pricing (Xu et al, 2020;Zhou and Xu, 2020), product research and development (Li, 2020;Xing, 2014) and product compatibility (Choi and Lee, 2017;Li and Chen, 2012). Regarding product pricing strategies, Yi and Yang (2017) analyzed the impact of indirect network externalities on manufacturers' wholesale prices and retailers' marketing strategies.…”
Section: Network Externalitiesmentioning
confidence: 99%
“…Current studies on network externalities mainly focus on product pricing (Xu et al. , 2020; Zhou and Xu, 2020), product research and development (Li, 2020; Xing, 2014) and product compatibility (Choi and Lee, 2017; Li and Chen, 2012). Regarding product pricing strategies, Yi and Yang (2017) analyzed the impact of indirect network externalities on manufacturers’ wholesale prices and retailers’ marketing strategies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Pal [34] analyzed the influences of network externalities using the Cournot game model and the Bertrand game model and found that if there are positive network externalities, the Bertrand model can lead to lower prices and corporate profits. Based on different decision-making models, Zhou and Xu [35] studied the impact of network externalities on the company's product pricing, market share, and profits. They found that in the model of a nonstrategic firm facing nonstrategic consumers, the increase in network externalities is beneficial to the profits of one company, but not to the profits of another company.…”
Section: Network Externalities In the Supply Chainmentioning
confidence: 99%
“…Companies generally focus on maximizing their total profits in the pricing decision-making process without considering the strategic behavior of consumers (Zhou & Xu, 2020) in their market segment. For example, business owners may determine margins excessively in price determination when they know that consumers do not know the market price information of the product.…”
Section: Introductionmentioning
confidence: 99%